2021
DOI: 10.3390/su13126905
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Interpretation through Guiding Tour, Quality of Reception and Relics’ Worship on the Satisfaction of Pilgrims Attending the Iasi Feast

Abstract: Recently, in line with the increased attention paid to cultural tourism in general and to religious tourism in particular, researchers and practitioners have become increasingly interested in the analysis of various aspects related to cultural heritage in order to capitalize on its value by means of its interpretation, thus providing beneficial effects both for tourists and for tourism’s sustainable development. The aim of this research is to analyze the extent to which the methods of interpretation of the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…They found that gender, age, occupation and academic background had no significant difference in customer satisfaction. In contrast, Tatarusanu, et al [ 54 ] investigated participating in the Saint Parascheva pilgrimage organized annually by Metropolitan Cathedral in Iasi, Romania. They found that only age and faith significantly impacted on satisfaction among the socio-demographic aspects of the study (age, education, area, income, gender, and faith).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that gender, age, occupation and academic background had no significant difference in customer satisfaction. In contrast, Tatarusanu, et al [ 54 ] investigated participating in the Saint Parascheva pilgrimage organized annually by Metropolitan Cathedral in Iasi, Romania. They found that only age and faith significantly impacted on satisfaction among the socio-demographic aspects of the study (age, education, area, income, gender, and faith).…”
Section: Discussionmentioning
confidence: 99%
“…Pilgrims with high and low income are more satisfied than those with average income. Another study about tourists participating in the “Saint Parascheva” pilgrimage, Romania, found that age variable is the only one among socio-demographic aspects that influenced the pilgrims’ satisfaction, which is attributed to the high level of faith among them [ 54 ]. Moreover, religious tourism does not indicate a relationship between sociodemographic variables and loyalty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the considerations that can improve services to visitors in the national park area is by involving more interpreters in the national park area (Dileep Kumar et al, 2020). In order to achieve optimum tourist satisfaction, interpretation programs and guided trips must be encouraged more optimally by the managers of the national park area (Moscardo, 2017;Beattie & Schneider, 2018;Xiang et al, 2020;Tatarusanu et al, 2021). Furthermore, one of the weaknesses in the implementation of the traveling method is the motivation of tourists in accepting the presence of a guide/interpreter on their tour.…”
Section: Tourist Community Managermentioning
confidence: 99%
“…The method of traveling around and telling stories is an appropriate method of involving the community. This method is a better approach for gaining emotional engagement with the landscape and its culture (Moscardo, 2017;Qi et al, 2017;Gao et al, 2018;Tatarusanu et al, 2021). In addition, this method can absorb a larger number of people to accompany tourists during the holiday seasons.…”
Section: Tourist Community Managermentioning
confidence: 99%
“…It's different when looking at a frog or aquatic plant around the waterfall. It is not discussed as it is not interesting and unrelated to satisfy the audience`s recreational needs (Moscardo, 2017;Tatarusanu, Butnaru, Nita, Neculaesei, & Ciortescu, 2021).…”
Section: Introductionmentioning
confidence: 99%